Socio-economic analysis of the EU citizens’ attitudes toward farmed animal welfare from the 2023 Eurobarometer polling survey - Riuzzi, Giorgia; Contiero, Barbara; Gottardo, Flaviana; Cozzi, Giulio; Peker, Arzu; Segato, Severino (Frontiers in Veterinary Science, 2025)
Background and methodsEuropeans’ expectations and opinions regarding the conditions and welfare of farmed animals have evolved continuously. Since 2005, the Eurobarometer (Eb) polling instrument has been used to monitor EU citizens’ attitudes towards farmed animal welfare (FAW). Using the last Eb survey (2023), this study categorized respondents into clusters according to their answers to 12 selected questions on FAW. The ultimate goal was to highlight trends useful to stakeholders and policymakers within the animal food supply chain to design and implement activity planning, progress, and information campaigns.Results and discussionAs the Eb data came from a stratified multi-stage, random (probability) sample design, the seven clusters sorted through our statistical approach reflected the opinions of the EU population in 2023. These clusters could be further merged into three macro-clusters with two main opposite levels of concern (>80% positive answers) about FAW: concerned about at least 10 questions (74% of the sample); concerned about no more than three questions (6% of the sample); and a third macro-cluster in between concerned about five to seven questions, especially on specific farming practices (20% of the sample). An analysis of the socioeconomic characteristics of the respondents within clusters (gender, age, education, occupation scale, geographical origin, and regular contact with animals) showed that the main discriminating features were gender, level of education, and regular contact with animals; women and well-educated people in regular contact with companion animals were more concerned about FAW overall. The analysis also highlighted divergent responses regarding shopping habits and information searches among the clusters.